Training Evaluation Using Kirkpatrick Evaluation Model for Well Intervention Pressure Control Training - Karnando; Krismadinata; Ambiyar; M. Giatman (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effectiveness of Well Intervention Pressure Control training using the Kirkpatrick Evaluation Model which includes four levels: Reaction, Learning, Behavior, and Outcomes. The research method used was a mixed methods approach combining quantitative and qualitative methods. The evaluation was conducted on 62 trainees working in the oil and gas sector, with a randomly selected sample. The results showed that the training was successful in improving participants' understanding of the training material, including pressure control procedures, as well as other technical skills. At the Reaction level, the majority of participants responded positively to the materials and teaching. At the Learning level, there was a significant increase in pre-test and post-test scores, indicating the success of the training in improving participants' knowledge. At the Behavior level, participants successfully applied the skills learned in real field situations, while at the Outcome level, the training was shown to improve operational performance and safety. In conclusion, the training successfully met its objectives of enhancing participants' technical skills and professional attitudes, and contributed to improved organizational performance, especially in terms of safety and operational efficiency in the oil and gas industry.